THE ROLE OF ZAKAT IN REDUCING POVERTY AND INCOME INEQUALITY AMONG NEW CONVERT (MUALLAF) IN SELANGOR, MALAYSIA - Johari, Fuadah; Ab Aziz, Muhammad Ridhwan; Mohd Ali, Ahmad Fahme (Online Journal of Research in Islamic Studies, 2014)
This study attempts to examine the effectiveness of monthly zakat distribution as a mechanism to poverty reduction among the new converts in the state of Selangor, Malaysia. The target population of this study is the new converts categories of the Selangor Zakat Centre (LZS) 1 zakat recipients. Simple Random sampling procedure is applied to collect primary data related to zakat recipients from the new convert category of the ten districts of Selangor. Poverty maps are derived based on the collected data. These facilitate an examination of the most affected area of poverty within the context of selected socio economic variables. The effects of zakat distribution on poverty are analysed within the context of burden of poverty; specifically in terms of incidence, intensity and severity of poverty. These are examined using four major indices of poverty, which include the Headcount Index, Average Poverty Gap, Income Gap and Sen Index. To measure the effect of zakat distribution towards the income inequality, this study uses the Gini Coefficient and Lorenz Curve. Results reveal that zakat distribution reduces poverty incidence, reduces the extent of poverty and lessens the severity of poverty. Although, the current practice of zakat distribution in Selangor only gives a small effect on increasing the income of the poor. Hence, by locating the perfect amount of zakat distribution to eliminate poverty and to offer alternative zakat distribution model is the best way in reducing the income inequality and maximization of social welfare. This study manage to identify the group most affected by income inequality and poverty will pave the way towards policies for a more effective and efficient utilization of scarce zakat resources.